Strategic Communication in Promoting Environmental Sustainability: A Case Study of Alfamart's Campaign for Reusable Tote Bags - Nugroho, Arnold Surya; Widjaya, Oey Hannes; Gede Sukada; Kurniawan, I Made Satria (Faculty of Communication Science | Universitas Pancasila Jakarta, Indonesia, 2023)
This case study examines Alfamart's strategic communication efforts to promote the use of reusable tote bags as part of their environmental sustainability initiative. Using qualitative data collected through semi-structured interviews with managers and customers, as well as document analysis, the study explores the effectiveness of Alfamart's communication strategies in raising awareness, shaping attitudes, and changing consumer behavior. The findings indicate that a well-coordinated multi- channel communication approach, integrating both online and offline methods, significantly increased customer awareness and knowledge about the environmental impact of plastic waste. This heightened awareness facilitated positive attitudinal changes and led to the adoption of reusable tote bags. The study also highlights the importance of incorporating customer feedback to refine and improve communication strategies continuously. Despite the overall success, challenges such as customer resistance due to convenience factors and logistical issues were identified, underscoring the need for ongoing communication efforts and operational adjustments. The results demonstrate the potential of strategic communication to promote environmental sustainability and drive meaningful behavior change.